An Integrated Autopsy based Study on Variations in Origin of Right and Left Hepatic Arteries & Cystic Artery in Light of Hepato-Biliary Surgery - Puloma Chakraborty; Sayak Sovan Dutta; Sandip Mukhopadhyay (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Laparoscopic Cholecystectomy is widely accepted as the gold standard in the treatment of cholelithiasis and this new technique was initially associated with a significant increase in morbidity, and in particular, in iatrogenic biliary injury and arterial haemorrhage, perhaps due to a lack of knowledge of the laparoscopic anatomy of the gallbladder pedicle.The arterial system of human body is often subjected to a good number of variations. Therefore, trying to find out variations in origin of right and left hepatic arteries and also cystic artery will surely be a useful endeavor for an Anatomist and Autopsy Surgeon, moreover such an effort will help the surgeons in planning and operating upon the hepatobiliary system. Method:The present work was carried out in the Department of FMT, NRSMCH, Kolkata in collaboration with the Department of Anatomy, Medical College, Kolkata over a period of one year to find out variations ion origin of right and left hepatic arteries and cystic artery. Fifty cadavers of both sexes were subjected to detail dissection method based on inclusion and exclusion criteria. The study was prospective, cross sectional, observational, autopsy based study.Conclusion:In 92% cases total number of branches from the HAP were three, four branches were arising from it in 6% cases, whereas >four branches from the HAP in remaining 2% cases.The branching pattern of the HAP at the porta hepatis showed bifurcation in 96 % cases, whereas HAP showed trifurcation pattern at porta hepatis in 4% cases.Any source of origin of the RHA and LHA other than the HAP was recorded as 0%. The percentage of occurrence of accessory or replaced RHA was 0%.This was also the case with LHA.The present study revealed the RHA (92%) being the commonest source of origin of cystic artery. In 8% cases cystic artery represented variant origin. Variant origins of CA were represented by the HAP (6%) and GDA (2%).In 96% of cases, the cystic artery was single. Remaining 4% of cadavers showed presence of more than one cystic artery, the number being two.Most significant finding in this present study according to the researcher is the presence of double cystic arteries.